RELATIONSHIP BETWEEN HEALTH SERVICES AND PATIENT SATISFACTION FROM THE SOCIAL SECURITY AGENCY (BPJS): A LITERATURE REVIEW - Endarwati, Wa Ode Khofifah; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Hospital is an establishment engaged in the provision of healthcare services. The government must ensure that individuals have access to health services, which is considered a fundamental right. Hospital is one type of facility that is established and operated by the government. Despite this, a significant number of Indonesians continue to lack access to health services Priority must be given to ensuring patient satisfaction when implementing services. An element contributing to patient discontentment is the inadequate level of attention provided by hospitals, particularly to inpatients utilizing Badan Penyelenggara Jaminan Sosial (BPJS) services. The research approach employed was a narrative review of articles retrieved from databases such as PubMed and Google Scholar, utilizing the search terms